Somerset Maugham, another physician-writer, between literature and the screen - María Silvia D’Ottavio‐Callegari; Alberto Enrique D’Ottavio‐Cattani; María Eugenia D’Ottavio‐Callegari (Revista de Medicina y Cine / Journal of Medicine and Movies, 2024)
Following the approach already employed in an earlier article on Archibald Joseph Cronin1, physician, and writer, this paper focuses on William Somerset Maugham, another physician who successfully ventured into literature, producing many plays, novels, and short stories adapted to the screen (cinema and TV), herein chronologically listed and described.